Full‐Temperature All‐Solid‐State Ti3C2Tx/Aramid Fiber Supercapacitor with Optimal Balance of Capacitive Performance and Flexibility. (24th March 2021) - Liu, Qi; Zhao, Anran; He, Xuexia; Li, Qi; Sun, Jie; Lei, Zhibin; Liu, Zong‐Huai
Abstract: Full‐temperature all‐solid‐state flexible symmetrical fiber supercapacitors (FSCs) are assembled by using montmorillonite flake/polyvinyl alcohol organic hydrogel (F‐MMT/PVA OHGE) as the electrolyte and separator and Ti3 C2 T x /ANF‐5% (T/A‐5) fiber as the electrode, in which T/A‐5 fiber is prepared by using delaminated Ti3 C2 T x nanosheets as assembled units and 5% of aramid nanofiber (ANF) as the functional additive using a wet spinning method in a coagulated bath with 0.5 m FeCl2 solution. The T/A‐5 hybrid fiber exhibits a specific capacity of 807 F cm −3 in 3 m H2 SO4 electrolyte, a superior mechanical strength of 104 MPa, and a high conductivity of 1025 S cm −1 . The assembled F‐MMT/PVA OHGE T/A‐5 FSC not only shows a specific capacitance of 295 F cm −3 and a capacitance retention of 91% at a current density of 5 A cm −3 after 10 000 charging/discharging cycles, but also a maximum volumetric energy density of 26.2 mWh cm −3 . Meanwhile, the assembled device displays good flexibility and excellent capacitance in a wide temperature range of −40 to 80 °C, the electrochemical performance of the FSC is maintained under varying degrees of bending. This study provides an effective strategy for designing and assembling of full‐temperature all‐solid‐state symmetrical flexible FSCs with the optimal balance of capacitive performance and flexibility. Abstract : A Ti3 C2 T x /ANF‐5% hybrid fiber with an optimal balance of the capacitance and flexibility is prepared by wet spinning method. A full‐temperature all‐solid‐state fiber supercapacitor is assembled on the basis of the Ti3 C2 T x /ANF‐5% fiber and developed organic hydrogel, which shows a maximum volumetric energy density of 26.2 mWh cm −3 and good flexibility in a wide temperature range of ‐40‐80 °C.